Analisis Pengaruh Riba Terhadap Tingkat Kemacetan di Ibu Kota Jakarta - Ruslan Husein Marasabessy (Jurnal Asy-Syukriyyah, 2018)
The first and foremost reason riba is haram is because Allah declared it so. It is based on Allah’s infinite wisdom that He deems an action to be obligatory or prohibited, prescribing matters in man’s best interests, in this life and in the Hereafter, as He is the All-Wise, All- Knowing. The scholars of Islam have suggested the following reasons as to why riba is haram:There are many proofs showing that riba is haram and one of the most serious sins in Islam.Abu Hurayra said, the Messenger of Allah (pbuh) said: A time will come over mankind when not a single person will remain who does not consume riba (usury, interest); and if one does not consume it, the vapor or dust of it will reach him.nowdays Living in a capitalist society makes it difficult to completely avoid riba.however, the threat is not enough for the community to avoid the usury case. the effect of usury in real terms must be clearly described, in order to raise public awareness.the consumption behavior of motor vehicles is one of the causes of congestion in urban areas, many people use usury (Leasing) to buy vehicles, There are many reasons why we suffer traffic jams every day. One of these is the rapid growth of the population. As a result of this, the number of cars is increasing annually. Jakarta was named the world city with the worst traffic in one index last year. An estimated 70% of the city’s air pollution comes from vehicles. this paper found that congestion in Jakarta is caused by usury, this can be seen from the high use of usury instruments in motor vehicle financing (leasing).